Bioequivalence and Safety of Levetiracetam Granules and Oral Solution: A Randomized, Single‐Dose, 2‐Period Crossover Study in Healthy Chinese Volunteers Under a Fasting Condition. Issue 3 (14th February 2022) - Liu, Yun; Zou, Yang; Wang, Yijun; Jiang, Fan; Xu, Wenjing; Liu, Shuyun; Jia, Jingying; Yu, Chen; Fang, Liming; Hu, Liwei; Zhang, Kanyin E.; Long, Jingwen; et al.
Abstract: The bioequivalence and safety of levetiracetam granules (test formulation) and oral solution (reference formulation) were evaluated in Chinese healthy volunteers under a fasting condition. A total of 24 subjects randomly received the test or reference formulation at the rate of 1:1. The alternative formulation was administered after a 7‐day washout period. The blood samples were collected at designated time points. Liquid chromatography–tandem mass spectrometry was applied to determine the plasma concentrations of levetiracetam. Adverse events were monitored and recorded. The 90% CIs for the geometric mean ratios of maximum plasma concentration, area under the plasma concentration–time curve from time 0 to the last quantifiable concentration, and area under the plasma concentration‐time curve from time 0 to infinity between test preparation and reference preparation were 95.5% to 110.7%, 100.2% to 105.3%, and 100.3% to 105.7%, respectively, all within an acceptable bioequivalence range of 80.00% 125.00%. Both test and reference preparations were well tolerated. The trial confirmed that a single dose of 500‐mg levetiracetam granules was bioequivalent to oral solution under a fasting condition, and may serve as a new dosage form of levetiracetam for clinical practice.